Karakteristik Pengusaha Islami dan Standar Harga Jual Barang - Faruk, Ahmad (TIN: Terapan Informatika Nusantara, 2020)
The economic crisis that occurred in 1999 proved that the principle of a sustainable economy is sharia. Including the behavior of entrepreneurs must also reflect Islamic principles. especially the current economy which is experiencing rapid development. Moreover, in the future the economy enters the digital 4.0 era, which demands business people to continue to innovate and keep up with the times. Among the criteria of entrepreneurs according to Islam are devotion to Allah, have an honest nature, prioritize obligations as Muslims, and like to give charity. Do not forget to tithe if indeed the results of his efforts reach size for zakat. This research is a research library (library research), where the research is carried out using books, articles, and other documents as a source of data in the study. According to the Shariah there is no standard of profit that must be obeyed by every trader. But fiqh scholars, especially the Islamic schools of thought and others, have put restrictions on profits not to exceed one third of the capital. This limit is considered reasonable because it contains benefits for sellers and buyers